Enriched environment ameliorates dexamethasone effects on emotional reactivity and metabolic parameters in mice. (3rd July 2020) - Delanogare, Eslen; de Souza, Raul Marin; Rosa, Giovana Karoline; Guanabara, Fernando Garcia; Rafacho, Alex; Moreira, Eduardo Luiz Gasnhar
Abstract: Convincing evidence shows that stress is associated with the development and course of psychiatric and metabolic disorders. The hypothalamic-pituitary-adrenal (HPA) axis mediates the stress response, a cascade of events that culminate in the release of glucocorticoids from the adrenal cortex. Chronic hypercortisolism typically characterizes stress-related illnesses, such as depression, anxiety, and metabolic syndrome. Considering previous studies pointing that environmental enrichment (EE) mitigates the deleterious effects of stress on neurobiological systems, we hypothesized that EE can confer resiliency against prolonged glucocorticoid administration-induced behavioral and metabolic alterations in mice. In this regard, three-month-old male Swiss mice were exposed to a four-week period of standard environment (SE) or EE. After this period, still in the respective environments, dexamethasone was administered intraperitoneally (i.p.) at a dose of 4 mg/kg, for 21 consecutive days, in order to generate the emotional-related behavioral outcomes, as previously described. It is demonstrated herein that EE prevents the dexamethasone-induced anxiety-like and passive stress-coping behaviors, as observed in the open field and tail suspension tests. Moreover, EE mitigated the hyperproteinemia and body weight loss induced by excess dexamethasone and decreased basal glucose levels. Taken together, these results support the hypothesis that EE attenuates the effects of chronic administration of synthetic glucocorticoids in mice, a strategy that may be translated to the clinical perspective.